Avalia????o da internet do futuro em ambientes virtuais: Uma Abordagem com a NovaGenesis - D'??vila, Victor Hugo Domingues (2021)
The increase in the demand for connectivity is something that recurs in all spheres of society. Global initiatives seek to internalize and democratize access to this public good. Seeking to meet the needs of Internet improvement, such as mobility, security and identification of objects on the network, several initiatives propose alternatives to the Internet architecture as it is currently known, the so-called Internet of the Future proposals. In this context, an important question is: how could we build a new name resolution system for the Internet if there were no Domain Name System (DNS) ? This work aims to conceptualize some of these initiatives and evaluate a Brazilian proposal: NovaGenesis. This proposal has innovative pillars, defining network elements by software. It also employs concepts such as native content distribution, separation of identifiers and locators, self-naming and name certification. The present work seeks to evaluate the NovaGenesis virtual environment and compare it with implementations in physical environments. For this, the work presents an environment proposal for experimentation and performance evaluation of name resolution scenarios in a local domain and proposes a test methodology to be used. The results prove the advantages of the test method in a developed virtual environment, as well as the advantages of NovaGenesis in name resolution with distributed and self-organizing network cache. It is concluded that NovaGenesis is an alternative with satisfactory performance in a local domain to expand the support for name resolution on the Internet, with storage of records in network cache and access via publish/subscribe communication model.